The impact of debt finance on financial performance of a firm: a case of Telone private limited - Muzeya, Liziwe (Midlands State University, 2018)
The main objective of the study research was to determine the impact of debt finance on financial performance using a case of a company in the telecommunications sector and which is not quoted at the Zimbabwe Stock Exchange: TelOne Pvt Ltd. The major issue that gave rise and prompted the researcher to study across this area was the increased levels in debt funding of projects in the organisation of which no increase in financial performance was being marked. The study employed a mixed approach in answer the research questions which were both quantitative and qualitative. The information and data was gathered from secondary and primary sources which consisted of financial statements and questionnaires as well as interviews with a population of 30 from which a sample of 20 was incorporated. The statistical packages used for analysis of quantitative data were Excel and SPSS 20 and the variables incorporated in the study included long term debt, short term debt, diversification and tangibility and these were the independent variables whereas ROA was the measure of financial performance and dependent variable of the study. The key findings of the study shows that debt funding was significantly and statistically negatively impacting on ROA of the organisation which was a measure of financial performance. The study results showed that at significance level of 5%, the relationship between debt capital and financial performance was significant at close to 4% and therefore the null hypothesis of the study was not rejected. The study further revealed that 68% of the variations in financial performance were explained by debt capital and diversification and this meant that the organisation was relying too much on debt capital. The study recommended the organisation to utilise debt capital as the last resort as the costs of debt capital were found to be outweighing the benefits generated from the debt funded projects.